The propensity for tropomyosin twisting in the presence and absence of F-actin - Rynkiewicz, Michael; Fischer, Stefan; Lehman, William (Archives of biochemistry and biophysics, 2016)
A canonical model of muscle α-tropomyosin (Tpm1.1), based on molecular-mechanics and electron microscopy of different contractile states, shows that the two-stranded coiled-coiled is pre-bent to present a specific molecular-face to the F-actin filament. This conformation is thought to facilitate both filament assembly and tropomyosin sliding across actin to modulate myosin-binding. However, to bind effectively to actin filaments, the 42 nm-long tropomyosin coiled-coil is not strictly canonical. Here, the mid-region of tropomyosin twists an additional ∼20° in order to better match the F-actin helix. In addition, the N- and C-terminal regions of tropomyosin polymerize head-to-tail to form continuous super-helical cables. In this case, 9 to 10 residue-long overlapping domains between adjacent molecules untwist relative to each other to accommodate orthogonal interactions between chains in the junctional four-helix nexus. Extensive molecular dynamics simulations show that the twisting and untwisting motions of tropomyosin vary appreciably along tropomyosin length, and in particular that substantial terminal domain winding and unwinding occurs whether tropomyosin is bound to F-actin or not. The local and regional twisting and untwisting do not appear to proceed in a concerted fashion, resembling more of a “wringing-type” behavior rather than a rotation.